Excessive health behaviors in sports: links of orthorexia nervosa and exercise addiction with well-being, exercise activity in sports categories, and gender effects - Wachten, Hanna; Wurst, Ramona; Paganini, Sarah; Strahler, Jana (Frontiers in Nutrition, 2024)
Background and aims Orthorexia nervosa (OrNe), the obsessive fixation on healthy eating, and exercise addiction (ExAdd) have been discussed as correlated excessive health behaviors with potential mental health implications. The role of gender- and sports-specific differences remains unclear. This study aimed to investigate the links of ExAdd, OrNe, and the non-pathological interest in healthy eating (healthy orthorexia; HeOr) with well-being and exercise activity in various sports, considering gender effects. Methods Data from two cross-sectional online surveys were combined (N = 1064, 73.5% women, age = 28.23±11.09), measuring ExAdd (Exercise Addiction Inventory Revised), OrNe and HeOr (Teruel Orthorexia Scale), well-being (WHO-5 Well-Being Index), exercise activity and sports (Physical Activity, Exercise, and Sport Questionnaire). Results Well-being correlated with OrNe among women (r = -.291) and not meaningfully with ExAdd and HeOr among men. Gender differences were not significant, except for the higher correlation of ExAdd with exercise activity in resistance and fitness sports among men. Regression analyses revealed that exercise activity, especially in health, resistance and fitness sports, was linked to HeOr, but not to OrNe. ExAdd was associated with exercise activity in endurance, resistance and fitness, ball and team, antigravitation, technical, aesthetic sports, and martial arts. Discussion Men’s well-being may slightly benefit from ExAdd and an interest in healthy eating, while obsessive healthy eating may reduce women’s well-being. Although exercise activity is associated with ExAdd in a wide variety of sports, it does not explain the link between ExAdd and OrNe. Preventive measures should consider gender-specific risks in excessive health behaviors.